2016
DOI: 10.1038/srep20894
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of RNF2 Is an Independent Predictor of Outcome in Patients with Urothelial Carcinoma of the Bladder Undergoing Radical Cystectomy

Abstract: RNF2 (ring finger protein 2) is frequently overexpressed in several types of human cancer, but the status of RNF2 amplification and expression in urothelial carcinoma of the bladder (UCB) and its clinical/prognostic significance is unclear. In this study, immunohistochemical analysis and fluorescence in situ hybridization (FISH) were used to examine the expression and amplification of RNF2 in 184 UCB patients after radical cystectomy. Overexpression of RNF2 was observed in 44.0% of UCBs and was found to signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…23 Li et al found that overexpression of RNF2 was an independent predictor of outcome in patients with urothelial carcinoma of the bladder undergoing radical cystectomy. 24 Chen et al suggested that miR-139-5p overexpression combined with inactivation of the MAPK signaling pathway can reverse the cisplatin resistance of ovarian cancer by suppressing RNF2. 25 In the present study, we found that RNF2 expression was significantly increased in GC tissues and positively correlated with TNM stage and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…23 Li et al found that overexpression of RNF2 was an independent predictor of outcome in patients with urothelial carcinoma of the bladder undergoing radical cystectomy. 24 Chen et al suggested that miR-139-5p overexpression combined with inactivation of the MAPK signaling pathway can reverse the cisplatin resistance of ovarian cancer by suppressing RNF2. 25 In the present study, we found that RNF2 expression was significantly increased in GC tissues and positively correlated with TNM stage and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…RNF2 was reported to act as an oncogene in gastric cancer, 23 lung squamous cell carcinoma, 24 mammary carcinoma, 25 and urothelial carcinoma of the bladder. 26 Li et al reported that over-expression of RNF2 played a crucial role in the prognosis of urothelial carcinoma of the bladder. 26 In the present study, we found that circRNA_100146 sponged miR-149-5p and promoted RNF2 expression, thus accelerating cell proliferation and invasion of bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Li et al reported that over-expression of RNF2 played a crucial role in the prognosis of urothelial carcinoma of the bladder. 26 In the present study, we found that circRNA_100146 sponged miR-149-5p and promoted RNF2 expression, thus accelerating cell proliferation and invasion of bladder cancer cells. As revealed by the clinical data analysis, RNF2 was over-expressed in bladder cancer and showed a positive correlation with circRNA_100146 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly several studies published up to now described worsening of prognoses with increased RNF2 expression in cancers of pancreas [ 14 ], esophagus [ 15 ], liver [ 16 ], urinary bladder [ 17 ] and ovary [ 18 ]. It is possible that spectrum of genes actively modulated by RNF2 changes in different cell types [ 10 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%